In Vitro and In Vivo Anti-Angiogenic Activities of Panduratin A - Lai, Siew Li; Cheah, Shiau Chuen; Wong, Pooi Fong; Noor, Suzita Mohd; Mustafa, Mohd Rais (Public Library of Science, 2012)
BACKGROUND: Targeting angiogenesis has emerged as an attractive and promising strategy in anti-cancer therapeutic development. The present study investigates the anti-angiogenic potential of Panduratin A (PA), a natural chalcone isolated from Boesenbergia rotunda by using both in vitro and in vivo assays. METHODOLOGY/PRINCIPAL FINDINGS: PA exerted selective cytotoxicity on human umbilical vein endothelial cells (HUVECs) with IC(50) value of 6.91±0.85 µM when compared to human normal fibroblast and normal liver epithelial cells. Assessment of the growth kinetics by cell impedance-based Real-Time Cell Analyzer showed that PA induced both cytotoxic and cytostatic effects on HUVECs, depending on the concentration used. Results also showed that PA suppressed VEGF-induced survival and proliferation of HUVECs. Furthermore, endothelial cell migration, invasion, and morphogenesis or tube formation demonstrated significant time- and dose-dependent inhibition by PA. PA also suppressed matrix metalloproteinase-2 (MMP-2) secretion and attenuated its activation to intermediate and active MMP-2. In addition, PA suppressed F-actin stress fiber formation to prevent migration of the endothelial cells. More importantly, anti-angiogenic potential of PA was also evidenced in two in vivo models. PA inhibited neo-vessels formation in murine Matrigel plugs, and angiogenesis in zebrafish embryos. CONCLUSIONS/SIGNIFICANCE: Taken together, our study demonstrated the distinctive anti-angiogenic properties of PA, both in vitro and in vivo. This report thus reveals another biological activity of PA in addition to its reported anti-inflammatory and anti-cancer activities, suggestive of PA's potential for development as an anti-angiogenic agent for cancer therapy.